Effect of Parental Support on Curiosity of School going Children - Shabana; Begum, Khalida (INDIAN EDUCATIONAL REVIEW, 2013)
The present study examined the impact of parental support on curiosity of school going children. By adopting the principle of stratified proportionate random sampling technique, three hundred school going children(19-14 years) were selected from various higher secondary schools as sample from Durg district of Chhattisgarh. Standardised tools used were parental support scale developed and standardised by Nandwana and Asawa (1971) and children’s curiosity scale developed and standardised by Kumar (1992). For the statistical analysis of data three way ANOVA was computed. The study revealed significant main effects of Parental support and gender on children curiosity but the main effect of type of school was found not to be significant at 0.05 levels. Interactional analysis indicated significant first and second order interaction effect of parental support, gender and type of school which were found to be significant at 0.01 level of significance.